Administrative behavior a study of decision-making processes in administrative organizations - Simon, Herbert A (New York Free Press, 1997)
In this fourth edition of his ground-breaking work, Herbert A. Simon applies his pioneering theory of human choice and administrative decision-making to concrete organizational problems. To commemorate the fiftieth anniversary of the book's original publication, Professor Simon enhances his timeless observations on the human decision-making process with commentaries examining new facets of organizational behavior. Investigating the impact of changing social values and modem technology on the operation of organizations, the new ideas featured in this revised edition update a book that has become a worldwide classic.
Includes bibliographical references and index.
Keywords: Management